The semantic link between common metaphors and their literal counterparts - a brief analysis / Yuthandy Maniam (Universiti Teknologi MARA, Terengganu, 1991)
Metaphors derive their forms and meanings from the vocabulary of common literal usage. This article seeks to describe the nature of the formal relationship between metaphors and their literal conterparts as well as the underlying semantic basis. Theoretic conclusions relating to the semantic link between the two are made on the basis of evidence obtained through an analysis of the meanings of a sample selection of commonly used metaphors.